Separator for electrochemical cell and method for manufacturing the same

The introduction of a free-standing ceramic composite separator (CSP) in lithium-ion batteries addresses the limitations of conventional ceramic-coated plastic separators, offering enhanced mechanical strength, thermal stability, and safety through its unique inorganic/organic composite structure.

JP2025038122AInactive Publication Date: 2025-03-18OPTODOT CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024221001
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-10-09
Filing Date
2024-12-17
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional ceramic-coated plastic separators (CCS) in lithium-ion batteries face challenges such as limited high-temperature stability, mechanical strength, and safety issues due to thermal shrinkage and poor thermal conductivity.

Method used

Development of a free-standing, substantially entirely ceramic composite separator (CSP) without a porous polymer substrate, comprising porous inorganic/organic composite layers with enhanced mechanical strength, thermal stability, and reduced swelling in non-aqueous electrolytes.

Benefits of technology

The CSP achieves improved mechanical strength, thermal stability, and safety by maintaining operation at elevated temperatures, withstanding nail piercing tests, and exhibiting reduced swelling and enhanced ionic conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038122000013
    Figure 2025038122000013
  • Figure 2025038122000014
    Figure 2025038122000014
  • Figure 2025038122000015
    Figure 2025038122000015
Patent Text Reader

Abstract

To provide an electrochemical cell that includes an improved composite separator that is free-standing and substantially all-ceramic without a porous polymer substrate, suitable for use in an electrochemical cell.SOLUTION: An electrochemical cell includes: an anode material disposed on an anode current collector; a cathode material disposed on a cathode current collector; and a separator assembly disposed between the anode material and the cathode material. Therein the separator assembly includes: a first separator layer; a second separator layer; and an intermediate layer disposed between the first separator layer and the second separator layer, and configured to prevent further operation of the electrochemical cell when a trigger condition is met.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims the benefit of and priority to U.S. Provisional Patent Application No. 62 / 569,964, filed October 9, 2017, the entire contents of which are incorporated herein by reference. STATEMENT REGARDING FEDERALLY SPONSORED RESEARCH OR DEVELOPMENT

[0002] This invention was made with Government support under W56HZV-13-C-0063 awarded by the Department of Defense. The United States Government has certain rights in this invention. [Technical field]

[0003] The present invention relates to separators for use in electrochemical cells, such as rechargeable lithium ion batteries, and methods of making the separators and electrochemical cells incorporating the separators. [Background technology]

[0004] Continuing improvements in electrical energy storage by using rechargeable lithium-ion batteries are particularly important in a wide range of applications, such as personal electronic devices, electric vehicles, home energy storage, renewable power generation storage, etc. For portable devices, improvements in high temperature operating stability, compactness, ease of manufacture, etc. are particularly important. In particular, the separator between the anode and cathode is a key element in lithium-ion batteries for use in electronic devices. Such separators have traditionally been made by disposing ceramic materials on one or both sides of a sheet of porous polymer substrate material, so-called ceramic-coated plastic separators (CCS), and have been disposed between the electrodes. One of several considerations for the material used for the separator is the tolerance to high temperatures during battery use, and plastic materials tend not to be suitable for very high temperatures. As lithium-ion batteries incorporate less safe high energy density electrode materials into larger energy density batteries of increasing size, such as 40 Ah to 100 Ah lithium-ion cells in multi-cell battery packs, ceramic coated plastic separators (CCS) do not provide the required high safety, such as forced short circuit nail penetration testing of the battery. Thermal contraction of the plastic polymer support material of the CCS, beginning at temperatures around 110°C, also limits the ability to vacuum dry the CCS or the CCS / electrode stack to remove residual moisture and other volatiles prior to filling the electrolyte into a dry lithium-ion cell. Additionally, the plastic polymer support material is an insulator and does not have the thermal conductivity to efficiently spread heat and provide higher safety during sudden heating events in the cell.

[0005] In view of the above problems associated with polymer substrates, techniques have been developed to form free-standing all-ceramic separators (CSPs) for use in electrochemical cells, as described, for example, in U.S. Patent Application Publication No. 2013 / 0171500 to Xu et al. and U.S. Patent Application Publication No. 2015 / 0030933 to Goetzen et al. One challenge with previous CSPs is to obtain sufficient mechanical strength for cell assembly without separator breakage, and to provide a high percent porosity of the separator required for acceptable ionic conductivity while withstanding the mechanical strength of cell cycling and not exhibiting degradation and incompatibility with battery cell chemistries. The demand for separator mechanical strength has increased significantly in recent years due to the large increase in cell assembly speeds to reduce battery costs. In addition to the mechanical strength of the separator, it is important for the separator to have a high elastic modulus, up to a maximum of 2% elongation, to avoid stretching during cell assembly, and a high level of flexibility to withstand bending and folding during cell assembly. Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above, it is an object of the present invention to provide an improved free-standing, substantially all-ceramic composite separator (CSP) without a porous polymer substrate that is suitable for use in electrochemical cells, such as lithium-ion cells. [Means for solving the problem]

[0007] In an exemplary embodiment of the present invention, electrochemical cells incorporating one or more porous inorganic / organic composite separator layers reach a peak temperature of up to 100° C. in a nail penetration test performed with a nail of about 3 mm diameter penetrating at approximately 80 mm / s.

[0008] In exemplary embodiments, electrochemical cells incorporating one or more inorganic / organic composite separator layers maintain operation at or below 150° C. for at least 3 hours, preferably at or below 200° C. for at least 2 hours, and more preferably at or below 100° C. for at least 30 hours when heated at the indicated temperatures for the indicated times in an accelerating rate calorimeter (ARC) test.

[0009] In an exemplary embodiment, the composite separator comprises one or more porous inorganic / organic composite separator layers having a total thickness of 20 microns or less, preferably 15 microns or less, and more preferably 12 microns or less.

[0010] In an exemplary embodiment, the composite separator comprises one or more porous inorganic / organic composite separator layers, which swell no more than 5%, preferably no more than 3%, after immersion in a non-aqueous electrolyte or propylene carbonate for 1 hour.

[0011] In an exemplary embodiment, the composite separator comprises one or more porous inorganic / organic composite separator layers having an overall resistance of 1.5 ohms or less, preferably 1.4 ohms or less, and more preferably 1.0 ohms or less.

[0012] In an exemplary embodiment, the composite separator comprises one or more porous inorganic / organic composite separator layers, the composite separator having a maximum tensile stress of at least about 1700 psi, a maximum tensile load of at least about 0.5 kg, and a percentage elongation at break of at least about 15%.

[0013] In an exemplary embodiment, the composite separator is made by coating one or more composite separator layers in a predetermined order onto a release substrate, peeling the layers from the release substrate, and vacuum drying the peeled layers at about 130° C.-150° C. for about 1 hour-4 hours to provide a free-standing composite separator.

[0014] In an exemplary embodiment, the multi-layer composite separator comprises a porous layer comprising particles and a polymer that is non-swellable in a non-aqueous electrolyte, and a porous inorganic / organic composite separator layer on one or both sides of the porous layer, the composite separator layer comprising a polymer that swells in the non-aqueous electrolyte.

[0015] In an exemplary embodiment, the particles comprise inorganic particles selected from the group consisting of inorganic oxides and inorganic nitrides.

[0016] In an exemplary embodiment, the inorganic particles comprise boehmite particles.

[0017] In an exemplary embodiment, the particles comprise polymer particles that are insoluble in water.

[0018] In an exemplary embodiment, the particles comprise polymer particles that are insoluble in propylene carbonate.

[0019] In an exemplary embodiment, the porous layer comprises a cross-linking agent that reacts with the polymer particles.

[0020] In an exemplary embodiment, the particles comprise inorganic particles selected from the group consisting of inorganic oxides and inorganic nitrides, and further comprise polymer particles that are insoluble in water.

[0021] In an exemplary embodiment, the polymer in the porous layer is polyvinyl alcohol.

[0022] In an exemplary embodiment, the polymer in the composite separator layer is polyvinylidene difluoride (PVdF).

[0023] In an exemplary embodiment, the composite separator layer comprises inorganic particles selected from the group consisting of inorganic oxides and inorganic nitrides.

[0024] In an exemplary embodiment, the inorganic particles comprise boehmite particles.

[0025] In an exemplary embodiment, the weight percentage of inorganic particles in the composite separator layer is between 60% and 95%.

[0026] In an exemplary embodiment, the composite separator layer is a xerogel layer.

[0027] In an exemplary embodiment, the porous layer is a safety shutdown layer.

[0028] In an exemplary embodiment, the multi-layer composite separator swells no more than 0.5% after immersion in an electrolyte for 1 hour.

[0029] In an exemplary embodiment, the multi-layer separator is made by coating a porous layer and one or more composite separator layers in a predetermined order onto a release substrate and peeling the layers from the release substrate to provide a free-standing multi-layer composite separator.

[0030] In an exemplary embodiment, each layer is provided by a coating process.

[0031] In an exemplary embodiment, the lamination step occurs after one or more coating steps.

[0032] In an exemplary embodiment, the multi-layer separator is compressed at its thickness in the narrow lane prior to slitting in the narrow lane to provide the desired width and increase mechanical strength along the edges of the multi-layer separator.

[0033] In an exemplary embodiment, the multi-layer composite separator comprises a porous layer formed by a phase inversion process comprising a polymer that is non-swellable in a non-aqueous electrolyte, and a porous inorganic / organic composite separator layer on one or both sides of the porous layer, the composite separator layer comprising a polymer that swells in a non-aqueous electrolyte.

[0034] Other features and advantages of the present invention will become readily apparent from the following detailed description and accompanying drawings. [Brief description of the drawings]

[0035] The above and related objects, features, and advantages of the present invention will be more fully understood by reference to the following detailed description of illustrative but preferred embodiments of the invention in connection with the accompanying drawings. [Figure 1A] FIG. 1A is a flow diagram illustrating a binder solution preparation process according to an exemplary embodiment of the present invention. [Figure 1B] FIG. 1B is a flow diagram illustrating a ceramic dispersion preparation process according to an exemplary embodiment of the present invention. [Figure 1C] FIG. 1C is a flow diagram illustrating a separator coating mixture preparation process according to an exemplary embodiment of the present invention. [Diagram 2] FIG. 2 is a top view of a mixing chamber according to an exemplary embodiment of the present invention. [Figure 3A] FIG. 3A is a graph reflecting the viscosity of the ceramic separator coating composite material resulting from the process 100c shown in FIG. 1C. [Figure 3B] FIG. 3B is a graph reflecting the particle size distribution of the ceramic separator coating composite material resulting from the process 100c shown in FIG. 1C. [Figure 3C-D-E-F-G] 3C, D, E, F, and G are cross-sectional side-view photomicrographs (scanning electron microscope, "SEM") of a CSP formed in accordance with an exemplary embodiment of the present invention, with C, D, E, F, and G being at different magnifications. [Figure 3H] FIG. 3H is a graph showing comparative pore size distribution of a coated and dried CSP formed in accordance with an exemplary embodiment of the present invention. [Figure 4] FIG. 4 is a representative diagram of an assembly for manufacturing a free-standing all-ceramic separator according to an exemplary embodiment of the present invention. [Diagram 5] FIG. 5 is a cross-sectional view of a shutdown layer disposed on a composite separator layer according to an exemplary embodiment of the invention. [Figure 6]FIG. 6 is a graphical plot reflecting the “Time vs. Temperature” results and the “Self-Heating Rate vs. Temperature” results in the ARC test for the “CSP1” cell with the CSP-A separator. [Figure 7] 7A, 7B, 7C, and 7D are graphical plots reflecting the "Time vs. Temperature" results and the "Self-Heating Rate vs. Temperature" results, respectively, in the ARC test for the "CSP2" cell with a 20 μm CSP-A separator. [Figure 8] 8A, 8B, 8C, and 8D are graphical plots reflecting the "time vs. temperature" results and the "self-heating rate vs. temperature" results, respectively, in an ARC test for a "shutdown on anode" (i.e., CSP-A separator with a shutdown layer near the anode) cell. [Figure 9] FIG. 9 shows the results of tests performed on the “CCS1 on anode” cell for comparison with the “shutdown on anode” cell. [Figure 10] FIG. 10 is a graphical plot reflecting the "Time vs. Temperature" results and the "Self-heating rate vs. Temperature" results in an ARC test for a "shutdown on cathode" (i.e., CSP-A separator with a shutdown layer adjacent to the cathode) cell. [Figure 11] FIG. 11 is a graph showing the results of tests performed on the “CCS2 on anode” cell for further comparison with the “shutdown on anode” cell. [Figure 12] FIG. 12 shows the results of tests performed on PE separator cells "Control 1" and "Control 2" for comparison with the "CSP" cell. [Figure 13] FIG. 13 shows the results of tests performed on PE separator cells "Control 1" and "Control 2" for comparison with the "CSP" cell. [Figure 14A] FIG. 14A is a selective plot of catastrophic heating events prior to complete cell failure of an electrochemical cell sample incorporating a separator made in accordance with an exemplary embodiment of the present invention. [Figure 14B]FIG. 14B is a selective plot of the sudden heating event prior to complete cell failure for the comparative sample. [Figure 15] FIG. 15 is a graph showing thermal conductivity results for separator samples made in accordance with exemplary embodiments of the present invention and comparative separator samples. [Figure 16A] FIG. 16A is a graphical plot of temperature and voltage versus duration of the nail penetration test for the control cell sample. [Figure 16B] FIG. 16B is a graphical plot of temperature and voltage versus duration of a nail penetration test for a CSP cell sample fabricated in accordance with an exemplary embodiment of the present invention. [Figure 16C] FIG. 16C is a graphical plot of temperature versus time in the nail penetration test for the control cell samples. [Figure 16D] FIG. 16D is a graphical plot of temperature versus time in a nail penetration test for a CSP cell sample made in accordance with an exemplary embodiment of the present invention. [Figure 17A] FIG. 17A is a graphical plot of life cycle test results for a control cell sample and cells incorporating various CSP dimensions fabricated in accordance with an exemplary embodiment of the present invention. [Figure 17B] FIG. 17B is a graphical plot of life cycle test results for control cell samples and cells incorporating various CSP dimensions fabricated in accordance with an exemplary embodiment of the present invention. [Figure 18A] FIG. 18A is a graphical plot of cycling rate capability test results for a control cell sample and cells incorporating various CSP dimensions fabricated in accordance with an exemplary embodiment of the present invention. [Figure 18B] FIG. 18B is a graphical plot of cycling rate capability test results for a control cell sample and cells incorporating various CSP dimensions fabricated in accordance with an exemplary embodiment of the present invention. [Figure 18C]FIG. 18C is a graphical plot of cycling rate capability test results for a control cell sample and cells incorporating various CSP dimensions fabricated in accordance with an exemplary embodiment of the present invention. [Figure 18D] FIG. 18D is a graphical plot of cycling rate capability test results for a control cell sample and cells incorporating various CSP dimensions fabricated in accordance with an exemplary embodiment of the present invention. [Figure 19A] FIG. 19A is a graphical plot of 28-day discharge capacity retention test results for a control cell sample and a cell incorporating a CSP constructed in accordance with an exemplary embodiment of the present invention. [Figure 19B] FIG. 19B is a graphical plot of 28-day voltage drop test results for a control cell sample and a cell incorporating a CSP made in accordance with an exemplary embodiment of the present invention. [Figure 20A] FIG. 20A is a graphical plot of one year discharge capacity retention test results for a control cell sample and a cell incorporating a CSP fabricated in accordance with an exemplary embodiment of the present invention. [Figure 20B] FIG. 20B is a graphical plot of one-year voltage drop test results for a control cell sample and a cell incorporating a CSP fabricated in accordance with an exemplary embodiment of the present invention. [Figure 21A] FIG. 21A is a graphical plot of discharge resistance test results for a control cell sample and a cell incorporating a CSP fabricated in accordance with an exemplary embodiment of the present invention. [Figure 21B] FIG. 21B is a graphical plot of discharge resistance test results for a control cell sample and a cell incorporating a CSP fabricated in accordance with an exemplary embodiment of the present invention. [Figure 21C] FIG. 21C is a graphical plot of discharge resistance test results for a control cell sample and a cell incorporating a CSP fabricated in accordance with an exemplary embodiment of the present invention. [Figure 22]FIG. 22 is a graphical plot of test results of thermally induced dimensional changes observed in control separator samples and separator samples made in accordance with exemplary embodiments of the present invention. [Figure 23A] FIG. 23A is a graphical plot of life cycle test results for cells incorporating separators made in accordance with embodiments of the present invention with various drying processes. [Figure 23B] FIG. 23B is a graphical plot of life cycle test results for cells incorporating separators made in accordance with embodiments of the invention with various drying processes. [Figure 23C] FIG. 23C is a graphical plot of life cycle test results for cells incorporating separators made in accordance with embodiments of the invention with various drying processes. [Figure 23D] FIG. 23D is a graphical plot of life cycle test results for cells incorporating separators made in accordance with embodiments of the invention with various drying processes. [Figure 23E] FIG. 23E is a graphical plot of life cycle test results for cells incorporating separators made in accordance with embodiments of the present invention with various drying processes. [Figure 24] FIG. 24 is a graphical plot of the comparative cycling rate capabilities of cells incorporating separators made in accordance with embodiments of the present invention. [Diagram 25] FIG. 25 is a graphical plot of cell voltage comparisons during pulse power testing of cells incorporating separators made in accordance with embodiments of the present invention. [Figure 26A] FIG. 26A is a graphical plot of testing results for mechanical properties of a separator made in accordance with an embodiment of the present invention before and after a drying process. [Figure 26B] FIG. 26B is a graphical plot of testing results for mechanical properties of a separator made in accordance with an embodiment of the present invention before and after a drying process. [Figure 26C]FIG. 26C is a graphical plot of testing results for mechanical properties of a separator made in accordance with an embodiment of the present invention before and after a drying process. [Figure 26D] FIG. 26D is a graphical plot of testing results for mechanical properties of a separator made in accordance with an embodiment of the present invention before and after a drying process. [Figure 26E] FIG. 26E is a graphical plot of testing results for mechanical properties of a separator made in accordance with an embodiment of the present invention before and after a drying process. [Figure 26F] FIG. 26F is a graphical plot of testing results for mechanical properties of a separator made in accordance with an embodiment of the present invention before and after a drying process. [Figure 26G] FIG. 26G is a graphical plot of testing results for mechanical properties of a separator made in accordance with an embodiment of the present invention before and after a drying process. [Figure 27A] FIG. 27A is a graphical plot of the test results for mechanical properties of a control separator and a separator made according to an embodiment of the invention after a calendaring process. [Figure 27B] FIG. 27B is a graphical plot of the test results for mechanical properties of a control separator and a separator made according to an embodiment of the invention after a calendaring process. [Figure 27C] FIG. 27C is a graphical plot of the test results for mechanical properties of a control separator and a separator made according to an embodiment of the invention after a calendaring process. [Figure 27D] FIG. 27D is a graphical plot of the test results for mechanical properties of a control separator and a separator made according to an embodiment of the invention after a calendaring process. [Figure 27E] FIG. 27E is a graphical plot of the test results for mechanical properties of a control separator and a separator made according to an embodiment of the invention after a calendaring process. [Figure 28A] FIG. 28A is a graphical plot of test results for mechanical properties of crosslinker coated separator samples made in accordance with embodiments of the present invention. [Figure 28B] FIG. 28B is a graphical plot of testing results for mechanical properties of crosslinker coated separator samples made in accordance with embodiments of the present invention. [Figure 28C] FIG. 28C is a graphical plot of testing results for mechanical properties of crosslinker coated separator samples made in accordance with an embodiment of the present invention. [Figure 28D] FIG. 28D is a graphical plot of testing results for mechanical properties of crosslinker coated separator samples made in accordance with embodiments of the present invention. [Figure 29A] FIG. 29A is a graphical plot of test results for mechanical properties of separator samples made according to embodiments of the present invention with specific crosslinker coating parameters. [Figure 29B] FIG. 29B is a graphical plot of test results for mechanical properties of separator samples made according to embodiments of the present invention with specific crosslinker coating parameters. [Figure 29C] FIG. 29C is a graphical plot of test results for mechanical properties of separator samples made according to embodiments of the present invention with specific crosslinker application parameters. [Figure 30A] FIG. 30A is a graphical plot of test results for mechanical properties of separator samples made according to embodiments of the present invention with specific crosslinker coatings. [Figure 30B] FIG. 30B is a graphical plot of test results for mechanical properties of separator samples made according to embodiments of the invention with specific crosslinker coatings. [Figure 30C] FIG. 30C is a graphical plot of test results for mechanical properties of separator samples made according to embodiments of the invention with specific crosslinker coatings. [Figure 31A]FIG. 31A is a graphical plot of test results for mechanical properties of separator samples made according to an embodiment of the invention with an edge reinforcement coating. [Figure 31B] FIG. 31B is a graphical plot of test results for mechanical properties of separator samples made according to an embodiment of the invention with edge reinforcement coating. [Figure 31C] FIG. 31C is a graphical plot of testing results for mechanical properties of separator samples made according to embodiments of the invention with edge reinforcement coatings. [Figure 31D] FIG. 31D is a graphical plot of testing results for mechanical properties of separator samples made according to embodiments of the invention with edge reinforcement coatings. [Figure 31E] FIG. 31E is a graphical plot of testing results for mechanical properties of separator samples made according to embodiments of the invention with edge reinforcement coatings. [Fig. 31F] FIG. 31F is a graphical plot of testing results for mechanical properties of separator samples made according to embodiments of the invention with edge reinforcement coatings. [Figure 31G] FIG. 31G is a graphical plot of testing results for mechanical properties of separator samples made according to embodiments of the invention with edge reinforcement coatings. [Figure 32A] FIG. 32A shows a cross-sectional view of a layer structure of a non-swelling porous layer and a CSP layer according to an exemplary embodiment of the present invention. [Figure 32B] FIG. 32B is a graph of test results showing the relationship between Gurley air permeability of laminated samples and weight fraction of non-swelling layer blend in accordance with an embodiment of the present invention. [Figure 32C] FIG. 32C is a graph of test results showing the relationship between the swell ratio (%) of laminated samples and the weight fraction of the non-swelling layer blend in accordance with an embodiment of the present invention. [Figure 33A] FIG. 33A is a diagram of test results for tensile stress for CSP separator samples made in accordance with an embodiment of the invention. [Figure 33B] FIG. 33B is a diagram of elongation test results for CSP separator samples made in accordance with an embodiment of the invention. [Figure 33C] FIG. 33C is a diagram of Gurley Air Permeability test results for CSP separator samples made in accordance with an embodiment of the invention. [Figure 33D] FIG. 33D is a diagram of impedance test results for CSP separator samples made in accordance with an embodiment of the invention. [Figure 33E] FIG. 33E is a graph of test results for % swell in propylene carbonate for CSP separator samples made in accordance with an embodiment of the invention. [Figure 34A] FIG. 34A is a diagram of test results before and after an extraction process for a CSP separator sample made in accordance with an embodiment of the invention. [Figure 34B] FIG. 34B is a diagram of test results before and after the extraction process for a CSP separator sample made in accordance with an embodiment of the invention. [Figure 34C] FIG. 34C is a diagram of test results before and after the extraction process for a CSP separator sample made in accordance with an embodiment of the invention. [Fig. 34D] FIG. 34D is a diagram of test results before and after the extraction process for a CSP separator sample made in accordance with an embodiment of the invention. [Figure 34E] FIG. 34E is a diagram of test results before and after the extraction process for a CSP separator sample made in accordance with an embodiment of the present invention. [Fig. 34F] FIG. 34F is a diagram of test results before and after the extraction process for a CSP separator sample made in accordance with an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] Reference will now be made in detail to the exemplary embodiments, which are illustrated in the accompanying drawings. Wherever possible, the same reference numbers are used throughout the drawings to refer to the same or like parts.

[0037] The term "substrate" refers to any supporting structure including, but not limited to, thin sheets or polymer separator layers of porous polymeric materials such as porous polyolefin substrates or layers used to make ceramic coated separators (CCS) or porous non-woven polymer substrates or layers used to make ceramic coated separators and ceramic impregnated separators. The term "substrate" also refers to thick but flexible sheets of plastic release film used in the methods of making embodiments of the present invention.

[0038] Free-standing composite separators without attached substrates, i.e., all-ceramic separators (CSPs), for use in electrochemical cells are desirable due to their ease of manufacture and cell fabrication, and their high temperature performance in comparison to conventional CCSs with polymer substrates. The present invention relates to techniques for forming separators comprising substantially ceramic materials applicable as free-standing elements disposed between electrodes in electrochemical cells. The present invention also relates to the CSPs themselves, including their chemical composition, formulation, physical properties, and performance characteristics.

[0039] I. Coating Mixture Process A process for forming a separator material according to an exemplary embodiment of the present invention is shown in Figures 1A, 1B, and 1C. First, Figure 1A is a flow diagram showing a binder solution preparation process 100a according to an exemplary embodiment of the present invention. Referring to Figure 1A, in step S110, a polymer resin such as polyvinylidene fluoride (PVdF) (e.g., Solef® 5130 available from Solvay Specialty Polymers) is added to a solvent such as N-methyl-2-pyrrolidone (NMP) with slow stirring in a mixing chamber. According to a preferred embodiment, the solvent is substantially all NMP to promote dissolution of the separator material and improved final coating rheology. Figure 2 shows a mixing chamber 200 according to an exemplary embodiment of the present invention in a plan view. As shown in FIG. 2, the mixing chamber 200 may be a cylindrical pail including one or more baffles 205 disposed along its circumferential inner wall to facilitate dissolution of the resin in process step S110. According to an exemplary embodiment of the invention, the inner wall of the mixing chamber 200 is fitted with an antistatic liner (not shown). Agitation may be provided by, for example, a Cowles blade 210 attached to an agitation shaft 215. For a 10 kg scale of binder formulation, the mixing chamber may have a 5 gallon capacity and is fitted with a four inch (4") Cowles blade 210. Correspondingly, 900 g of PVdf resin may be added to 9.1 kg of NMP in step S110.

[0040] After the PVdF resin is added, in step S120 of FIG. 1A, the stirring speed of the stirring shaft 215 is increased to 2650 RPM and the mixture is stirred for about 60 minutes. According to a preferred embodiment, the mixture is stirred at an elevated temperature, for example between about 40-60° C., to promote complete solubilization of the PVdF binder and minimize the possibility of the mixture retaining a partially soluble gel. Additionally, in a preferred embodiment of the present invention, a coles blade 210 is used to increase shear forces, thereby enhancing solubilization. In particular, the PVdf polymer has a very high molecular weight of about 1,000,000 Daltons and a high solids content of 9%, which makes it very viscous and requires aggressive stirring to completely dissolve. After stirring, the mixture is cooled to room temperature in step S125.

[0041] FIG. 1B is a flow diagram showing a ceramic dispersion preparation process 100b according to an exemplary embodiment of the present invention. In a preferred embodiment of the present invention, boehmite is used as the main ceramic material for forming the separator. Referring to FIG. 1B, in step S130, ceramic material such as boehmite particles (e.g., in powder form) is added to a solvent such as NMP under low-speed (e.g., 500 rpm) stirring in a mixing chamber, such as the mixing chamber 200 shown in FIG. 2. In a preferred embodiment, the solvent is substantially all NMP to improve the final coating rheology and finer dispersion of the preferred blend of boehmite. Also, in step S130, two or more different grades of boehmite material may be added in a predetermined order with their respective ratios, rates, and durations. In a preferred embodiment, in step S130, a hydrophobically modified grade of boehmite is added first. For a 10 kg scale ceramic dispersion preparation corresponding to the binder preparation shown in FIG. 1A, 5 kg of boehmite may be added to 5 kg of NMP in step S130.

[0042] After the boehmite is added, in step S140, the stirring speed of the stirring shaft 215 is increased to 2650 RPM and the mixture is stirred for about 60 minutes. According to a preferred embodiment, the mixture is stirred at an elevated temperature, for example, between about 40-60° C., to promote complete dispersion. After stirring, in step S145, the mixture is cooled to room temperature.

[0043] Referring now to FIG. 1C, a process 100c is described in which the binder solution and the ceramic dispersion formed in the processes 100a and 100b shown in FIG. 1A and 1B, respectively, are mixed to form a separator material (coating mixture). As shown in FIG. 1C, in step S150, the binder solution, for example the binder solution formed by the process 100a shown in FIG. 1A, is added to a solvent, such as NMP, in a mixing chamber, for example the mixing chamber 200 shown in FIG. 2, with gentle agitation. According to a preferred embodiment, the solvent is substantially all NMP to facilitate dissolution of the separator material and final coating rheology. For a 10 kg scale, about 4444 g of the binder solution (9% non-volatiles or NV) may be diluted with about 2756 g of NMP in step S150.

[0044] After diluting the binder solution, in step S160, the stirring speed of the stirring shaft 215 is increased to 1000 RPM and a ceramic dispersion, for example, a boehmite dispersion formed by process 100b shown in FIG. 1B, is added. In step S170, the stirring speed is maintained at 1000 RPM or adjusted, if necessary, for about 30 minutes to ensure fluid turnover while minimizing air entrainment. According to a preferred embodiment, the mixture is stirred at an elevated temperature, for example, between about 40-60° C., to promote complete homogenous mixing. For a 10 kg scale, about 2.8 kg of boehmite dispersion (50% NV) may be added in step S160. In a preferred embodiment, the mixture is stirred in the mixing chamber 200 with a coles blade 210 at high mixing and shear forces to prevent irreversible agglomeration of the boehmite particles that may result in a larger / broader final particle size distribution. After stirring, in step S175, the mixture is cooled to room temperature.

[0045] According to an exemplary embodiment of the present invention, coating mixtures for producing CSP separators may be formed by processes 100a-100c shown in Figures 1A-1C with varying ratios of each grade of ceramic material and binder material.

[0046] Example 1 As examples, four specific types of CSP separators having prescribed approximate material ratios were fabricated with satisfactory test results as shown in Table 1 below.

[0047] [Table 1]

[0048] Properties of boehmite pigments from Sasol, Lake Charles, LA and Duren, Germany are summarized below. <Chemical and physical properties of Sasol Dispal (registered trademark) 10F4> Al2O3(%):83 H3COO-(%):0.25 Loose bulk density (g / l): 550 Particle size (d50)(μm):30 Surface area (BET) * (m2 / g):100 Pore ​​volume * (ml / g):0.8 Crystal size (120)(nm):40 Dispersion particle size (nm): 240 Measurements at PCS: Measurements in a disc centrifuge: Surface Treatment:- <Chemical and physical properties of Sasol Disperal (registered trademark) 60> Al2O3(%):80 H3COO-(%):- Loose bulk density (g / l): 300~500 Particle size(d50)(μm):35 Surface area (BET) * (m2 / g):95 Pore ​​volume * (ml / g):0.9 Crystal size (120)(nm):60 Dispersed particle size (nm): Less than Measurement at PCS: 350 Measurement in disc centrifuge: 250 Surface Treatment:- <Chemical and physical properties of Sasol Dispal (registered trademark) 10SR> Al2O3(%):78 H3COO-(%):- Loose bulk density (g / l): - Particle size (d50)(μm):30 Surface area (BET) * (m2 / g):100 Pore ​​volume * (ml / g):0.8 Crystal size (120)(nm):40 Dispersion particle size (nm): Not applicable Measurements at PCS: Measurements in a disc centrifuge: Surface treatment: p-toluenesulfonic acid ( * Activated at 550℃ for 3 hours)

[0049] In this and subsequent examples of tests performed on CSP-A, CSP-B, CSP-B2, and CSP-B3 separators, 10F4 boehmite was surface treated with formic acid, and 10SR boehmite was surface treated with p-toluenesulfonic acid (p-TSA). Surface treating the boehmite particles with formic acid makes the boehmite more dispersible in water and in protic solvents such as alcohol, but not dispersible in NMP, which is one of the few aprotic solvents that can completely dissolve PVdF at 3 wt. % and higher solids. As used herein, the terms "insoluble" and "not soluble" mean that less than 3 wt. % of the material was dissolved or soluble in a particular solvent or water at room temperature or 25° C. Surface treating the boehmite particles with p-toluenesulfonic acid allows for dispersion in NMP. Based on the description herein, one skilled in the art will appreciate that the material ratios, surface treatments of each particle, etc. may be varied without departing from the spirit and scope of the present invention. Various types of inorganic particles such as boehmite, with or without surface treatment, may be blended in different ratios to form the CSP separator layer. For example, the ratio of boehmite 1 to boehmite 2 may be increased from 60%-40% by weight, as in CSP-B2 and CSP-B3, to 75%-25% by weight or less. This increase in the ratio of boehmite 1 to boehmite 2 may be accompanied by a corresponding increase in the P:B ratio. Other blends of inorganic particles may be similarly adjusted along with the P:B ratio to maintain or increase the porosity and rate capability of the resulting separator while maintaining or increasing mechanical strength and reducing swelling in organic carbonate solvents and electrolytes.

[0050] II. Mixed filtration Considering the high filler loading, optimized boehmite particle size distribution, and blend ratio of surface-treated / "un-treated" (e.g., 10SR / 10F4 or 10SR / D60 as mentioned above), this inevitably results in a small amount of large (>10 micron) agglomerates that need to be removed to optimize separator performance. According to an exemplary embodiment, prior to the die coating process, appropriate filtration of the coating mixture is performed with a filter pore size of about 10-25 microns.

[0051] Example 2 Samples of coating mixtures according to the above-mentioned processes 100a-100c shown in Figures 1A-1C were prepared for characterization. In particular, in this example, samples were prepared with ratios conforming to CSP-A as described in Example 1. Figures 3A and 3B are graphs reflecting the viscosity profile and particle size distribution, respectively, of the CSP-A ceramic separator coating mixture material obtained from process 100c shown in Figure 1C. Using a Brookfield viscometer with a #63 spindle, the viscosity of the 18% V coating mixture at 23°C ranged from 5,000 cPs at a spindle speed of 5 rpm to 3,000 cPs at a spindle speed of 30 rpm. As shown in Figure 3B. The CSP-A coating mixtures exhibited a significant particle size concentration around a median of 129 nm with a narrow distribution range for the majority of the mixture and with some large agglomerates with particle size diameters ranging from about 1.5 microns to about 30 microns. These larger agglomerates may be substantially reduced by appropriate filtration of the coating mixture. The narrow particle size distribution is reflected in the micrographs of Figures 3C, 3D, 3E, 3F, and 3G, which show relatively uniform particle sizes. The boehmite particles used in this Example 2 have an approximately cubic shape.

[0052] Correspondingly, as reflected in FIG. 3H, the CSP-A separator sample exhibited a narrow pore size distribution around 35 nm, as seen in the highest narrow peak in FIG. 3H. This pore size peak is similar to the primary particle crystal size of both of the two different boehmite particles in the CSP-A separator. The CSP-B and CSP-B2 separator samples showed corresponding narrow distributions around 50 nm and 60 nm, respectively, which are intermediate between the primary particle crystal size of the two grades of boehmite particles in the CSP-B and CSP-B2 separators. The other two pore size curves in FIG. 3H are for two different commercial ceramic coated separators (CCS). One CCS curve shows relatively broad pore size diameter peaks at about 0.1 microns and about 0.9 microns, which are superimposed on a very broad pore size distribution curve typical of a polymer substrate, from about 20 nm, i.e., about 0.02 microns, to about 0.6 microns, with a broad peak at about 80 nm, i.e., about 0.08 microns. The other CCS curve shows a relatively broad pore size peak for the ceramic coating at about 0.4 microns, which is superimposed on a very broad pore size curve of the polymer substrate.

[0053] III. Ceramic Die Coating Process A process for making a thin film ceramic precursor to a CSP separator according to an exemplary embodiment of the invention is shown in Figure 4. First, a thick non-porous polymer substrate 405, for example, a reusable release liner made of 125 μm PET (polyethylene terephthalate) with one or two side coating, as shown in Figure 4, is placed in correspondence with one or more ceramic coating mixture dispensers 410a on either side, and optionally in correspondence with another dispenser 410b. The liner 405, or the dispensers 410a and 410b, may be transported in the machine direction (MD), while the ceramic coating mixture resulting from the process 100c is dispensed from the dispensers 410a and 410b. According to an exemplary embodiment of the invention, the coating mixture is dispensed by slot die coating on the reusable release liner at a width of about 1.5 to 2 meters and a MD line speed of up to about 125 m / min, or by continuous belt casting. The dried mixture is formed into films 415a and 415b with thicknesses of about 6-20 μm, as shown in Figure 4. Films 415a and 415b (optional) obtained from dispensers 410a and 410b, respectively, on opposing sides of liner 405 are then removed from liner 405 by peeling to form free-standing porous CSP film separators for further processing as described below.

[0054] According to an exemplary embodiment of the invention, films 415a and 415b are removed from liner 405 and slit to width for assembly into a battery cell. As described further below, vacuum drying may be performed before and / or after assembling films 415a and 415b into a cell prior to filling the cell with electrolyte.

[0055] Given the high filler loading, high viscosity, certain preferred solvent systems (NMP), and certain rheological properties, pumping the coating mixture fluid to (and through) the coating dies, such as dispensers 410a and 410b, can present unique challenges. According to an exemplary embodiment of the invention, progressive cavity pumps may be used to supply dispensers 410a and 410b with appropriate NMP resistant fittings to allow for continuous use without degradation of the pumps or coating fluid.

[0056] IV. Cell Manufacturing Following die coating, according to an exemplary embodiment of the invention, as described in more detail below, the film 415a (and / or) 415b may undergo one or more processes for property improvement, including, but not limited to, one or more of vacuum drying (VD), crosslinking (or crosslinker coating), and edge reinforcement (ER). As described in more detail below, VD may be performed before and / or after the cell stack or inserting the cell stack into a casing (and before electrolyte filling). Also, as described in more detail below, separators made by die coated films (415a and / or 415b) as well as alternative coating methods such as gravure coating may include multiple ceramic coating layers and may be incorporated with one or more non-swelling layers and / or safety shutdown layers prior to cell fabrication according to an exemplary embodiment of the invention.

[0057] When ready for cell manufacturing, the slit separator films (415a and / or 415b) are wound into reel form for cell lamination. Cell lamination can be accomplished by many known processes, and the property improvements to the separator films (415a and / or 415b) discussed above and below address challenges presented by such cell lamination and associated cell manufacturing processes, for example, edge reinforcement treatments to the separator films (415a and / or 415b) improve edge tear resistance, particularly during handling of the films through cell lamination and manufacturing machinery.

[0058] According to an exemplary embodiment of the invention, the separator film (415a and / or 415b) in reel form is pulled through a z-fold lamination machine at a central "stacking" location. Cell lamination is preferably performed in a clean room environment. The separator is then folded back and forth as the anodes and cathodes are placed on the laminate. Once the laminate is built with enough electrode layers (e.g., 17 cathodes and 18 anodes in the laminate), the separator is wrapped around the laminate a predetermined number of times and cut / taped to form the "Dry Cell Laminate". The "Dry Cell Laminate" is then moved to a tabming / welding station, e.g., ultrasonic welding, to connect the anode and cathode tabs to create two respective leads (positive and negative). The tabbed cell is then placed in a HiPot (defect) tester where a high voltage is applied for a short period of time. If the separator has a hole or other defect that shorts the cell or causes the current to jump, the cell is rejected. The accepted laminates are then placed into a casing, such as a pouch, and sealed leaving an opening in the pouch for adding electrolyte through such an opening. Once the electrolyte filling process is complete, the pouch is fully sealed. The cells then undergo a final cell formation process, which may include heating the cell to form gases that are then removed by opening the pouch and resealing the pouch. The cells may be cycled (charged and discharged) a predetermined number of times in the cell formation process before being sold as a finished cell product for end use.

[0059] V. Shutdown Layer According to an exemplary embodiment of the present invention, one or more shutdown layers of a porous thermally fusible particle-filled coating may be disposed on one or both sides of a ceramic-based nanocomposite to form a free-standing CSP separator. The shutdown layer may be intermediate two ceramic-based nanocomposite layers. FIG. 5 shows a schematic cross-sectional view of a CSP separator incorporating a shutdown layer that may be disposed on a surface adjacent the anode and / or cathode of a lithium-ion battery during fabrication. As shown in FIG. 5, the ceramic-based (e.g., boehmite) nanocomposite layer may have a thickness of about 6-20 μm, and the shutdown layer coating may have a thickness of about 2-6 μm. In the cell, the shutdown layer functions to shut down the flow of lithium ions when the cell overheats, such as to 110° C., thereby shutting down the operation of the cell and preventing further discharge of the cell's energy. This shutdown of the cell's operation is due to a significant increase in the impedance or resistance of the cell due to loss of porosity in the separator. This loss of porosity upon heating in the cells corresponds to a large increase in the Gurley air permeability number for the separator when heated.

[0060] Example 3 The thermal stability of lithium ion cells comprising the CSP films prepared by the above method was tested. In particular, accelerated rate calorimetry (ARC) was performed on such lithium ion cells at a rated discharge capacity of about 5 Ah for cells with a variety of different separators, all in the form of a pouch. a. Two ceramic (only) membranes (20 micron "CSP" in CSP-A design); b. Two ceramic-coated polyolefin separators ("CCS shutdown on anode"); c. One ceramic (only) membrane with a shutdown coating facing the negative electrode (CSP-A) ("shutdown on anode"); d. One ceramic (only) membrane with a shutdown coating facing the positive electrode (CSP-A) ("shutdown on cathode"); e. Two controls (16 micron polyolefin (PE) separator).

[0061] For the "CSP" ARC test in this example, a pouch cell with a CSP-A version separator was used. The cell was fully charged using a CC / CV charging protocol with a 0.5C charge rate, 4.20V charge cutoff voltage, and a C / 20 rate tapered charge cutoff. The cell used a lithium nickel manganese cobalt oxide (NMC) positive electrode chemistry and a carbon (graphite) negative electrode chemistry. Excess pouch material was folded and taped. Insulated wire was connected to the cell tab and then to an external data logger for voltage measurements during testing. The cell was placed in an accelerating rate calorimeter (ARC) chamber and a thermocouple was attached to the side of the pouch using high temperature tape.

[0062] The ARC test is performed in "Heat-Wait-Search" mode, in which the ARC heats the chamber to a starting temperature of 50°C and waits until the sample temperature matches the chamber temperature. The system then waits a prescribed time while searching for heat generation from the sample. If no heat generation is detected, the system heats the chamber and sample to the next step (heat step = 5°C). If heat generation above the threshold is detected, the ARC continues to match the chamber temperature to the sample temperature and does not undergo any more heating steps (adiabatic region). The results are shown in Table 2.

[0063] [Table 2]

[0064] Referring to Table 2, when tested in an adiabatic environment (no heat loss to the surroundings), the cells began to self-heat with the following characteristics: CSP-A cells (i.e., "CSP1" and "CSP2") (2 tests) showed self-heating onset when the cell temperature exceeded 150°C. The other cells tested exhibited onset temperatures between 87°C and 129°C, except for one specific "CCS on anode" sample, where onset occurred at 145°C. The cell voltage behavior (e.g., shutdown or separator failure) was dependent on the separator material. Except for one specific "CCS on anode" sample, cells with polymer separators (full or partial) exhibited a voltage drop around 130°C, which coincides with the melting temperature of common polymer polyethylene (PE) separator materials. The two "CSP" cells maintained cell voltage until the cell temperature exceeded 190°C. Complete cell failure (d 2 T / dt 2 >100℃ / min 2 A sudden heating event was evident in most cells before the onset of self-heating (defined as the onset of self-heating at about 120°C). In the non-"CSP" cells, heating events were observed between 120°C and 170°C, except for one specific "CCS on anode" sample where the onset of heat generation exceeded 200°C (the other polymer separator cells showed an onset of heat generation at about 130°C). In both "CSP" cells, the heating event occurred at temperatures above 200°C, which was likely triggered by the opening of the pouch cell and the release of volatile electrolyte solvent. As reflected in these results, the tested CSP cells did not shrink even at temperatures above 220°C, maintained operation to higher temperatures versus the comparative cells, and both the self-heating onset temperature and voltage drop temperature were higher. The improved results, at least versus the "CCS" and "Control" samples, are attributed to the absence of a porous polymer substrate that shrinks and melts at about 130°C.

[0065] Figures 6A, 6B, 6C, and 6D are graph plots reflecting the "Time vs. Temperature" results and the "Self-Heating Rate vs. Temperature" results, respectively, in the ARC test for the "CSP1" cell with a 20 μm thick CSP-A separator. Figures 6B and 6D are enlarged portions of Figures 6A and 6C, respectively. The "CSP1" cell was tested at an open circuit voltage of 4.1410 V. As shown in Figures 6A-6D, the specific results over time of the ARC test were as follows: a. Temperature (℃): i. Start:157.5 ii. Sudden voltage drop: 192.0 b. Time (hours): i. Start:30.1 ii. Voltage drop: 32.2

[0066] 7A, 7B, 7C, and 7D are graph plots reflecting the "time vs. temperature" results and the "self-heating rate vs. temperature" results, respectively, in the ARC test for the "CSP2" cell with a 20 μm CSP-A separator. FIGS. 7B and 7D are enlarged portions of FIGS. 7A and 7C, respectively. The "CSP2" cell was tested at an open circuit voltage of 4.126 V. As shown in FIGS. 7A-7D, the specific time course results of the ARC test largely correspond to the "CSP1" results shown in FIGS. 6A-6D, as follows: a. Temperature (℃): i. Start:152.2 ii. Sudden voltage drop: 204.3 iii. Ventilation: 110 b. Time (hours): i. Start:30.1 ii. Voltage drop: 32.2 iii. Ventilation: 14

[0067] As shown in Figure 7A, the cell voltage was recorded at "0V" for several hours in the middle of the test, which may have been due to the expansion of the cell pouch during heating. Figures 7C and 7D show possible cell venting at 110°C, which is typically noted by a sudden drop in the cell temperature (and self-heating rate) while the cell is self-heating in adiabatic conditions.

[0068] 8A, 8B, 8C, and 8D are graphical plots reflecting the "time vs. temperature" results and the "self-heating rate vs. temperature" results, respectively, in the ARC test for the "shutdown on anode" (i.e., CSP-A separator with a shutdown layer near the anode) cell. FIGS. 8B and 8D are enlarged portions of FIGS. 8A and 8C, respectively. The cell was tested at an open circuit voltage of 4.108 V. As shown in FIGS. 8A-8D, the specific results over time of the ARC test were as follows: a.Temperature (℃): i. Start: 102.2 ii. Sudden voltage drop: 166.0 b. Time (hours): i. Start: 11.7 ii. Voltage drop: 20.8

[0069] Tests were performed on the "CCS1 on anode" cells for comparison with the "shutdown on anode" cells. The results are shown in Figures 9A-9D. Figures 9B and 9D are enlarged portions of Figures 9A and 9C, respectively. The cells were tested at an open circuit voltage of 4.131 V. As shown in Figures 9A-9D, certain time-dependent results of the ARC tests, with notable deficiencies when compared to the "shutdown on anode", were as follows: a.Temperature (℃): i. Start:87.1 ii. Sudden voltage drop: 129.0 iii. Ventilation: 144.5 (plot) b. Time (hours): i. Start: 8.6 ii. Voltage drop: 14.9 iii. Ventilation: 14.9

[0070] 10A, 10B, 10C, and 10D are graphical plots reflecting the "time vs. temperature" results and the "self-heat rate vs. temperature" results, respectively, in the ARC test for the "shutdown on cathode" (i.e., CSP-A separator with a shutdown layer adjacent to the cathode) cell. FIGS. 10B and 10D are enlarged portions of FIGS. 10A and 10C, respectively. The cell was tested at an open circuit voltage of 4.122 V. As shown in FIGS. 10A-10D, the specific results over time of the ARC test were as follows: a.Temperature (℃): i. Start:91.0 ii. Sudden voltage drop: 105.1 b. Time (hours): i. Start: 6.0 ii. Voltage drop: 8.7

[0071] Achieving shutdown at 105°C has been a long-desired outcome for lithium-ion cells, as lithium-ion cells typically undergo rapid thermal runaway at about 110°C, and it is important to terminate cell operation before the thermal runaway temperature is reached. Furthermore, for safety and cell performance reasons, lithium-ion cells should not be used after reaching about 100°C and any degradation of the cell has occurred, and shutting down the cell at 105°C automatically stops further use and operation of the lithium-ion cell. As can be seen from the examples below, CCS and PE separators with PE substrates do not shut down until significantly higher temperatures, such as 120°C-130°C or higher, and produce high heat generation and cell combustion at those temperatures, and are therefore not safety shutdown layers that reliably prevent combustion and explosion of lithium-ion electrochemical cells containing volatile and flammable organic electrolyte solvents.

[0072] For further comparison with the "Shutdown on Anode" cell, tests were performed on the "CCS2 on Anode" cell. The results are shown in Figures 11A-11D. Figures 11B and 11D are enlarged portions of Figures 11A and 11C, respectively. The cell was tested at an open circuit voltage of 4.122 V. As shown in Figures 11A-11D, the specific time-dependent results of the ARC test were as follows: a.Temperature (℃): i. Start:145.1 ii. Sudden voltage drop: 167.0 b. Time (hours): i. Start:20.9 ii. Voltage drop: 22.4

[0073] Finally, tests were performed on PE separator cells "Control 1" and "Control 2" for comparison with the "CSP" cells. The results are shown in Figures 12A-12D and 13A-13D, respectively. For "Control 1", Figures 12B and 12D are enlarged portions of Figures 12A and 12C, respectively. The "Control 1" cell was tested at an open circuit voltage of 4.154V. As shown in Figures 12A-12D, the specific time course results of the ARC test, with notable deficiencies when compared to "CSP1" and "CSP2", were as follows: a.Temperature (℃): i. Start:122.6 ii. Sudden voltage drop: 128.7 b. Time (hours): i. Start: 19.1 ii. Voltage drop: 19.2

[0074] For "Control 2," Figures 13B and 13D are enlarged portions of Figures 13A and 13C, respectively. The "Control 2" cell was tested at an open circuit voltage of 4.192 V. As shown in Figures 13A-13D, the specific time course results of the ARC test, with notable defects when compared to "CSP1" and "CSP2," were as follows: a.Temperature (℃): i. Start:129.1 ii. Sudden voltage drop: 126.9 b. Time (hours): i. Start: 18.2 ii. Voltage drop: 17.4

[0075] In summary, the "CSP1" and "CSP2" cells showed a significant improvement in thermal stability, especially compared to the conventional CCS and PE "Control1" and "Control2" cells. Figures 14A and 14B show the sudden heating events (d 2 T / dt 2 >100℃ / min 2 , i.e., the second derivative of the heat rate). As shown in these figures and in Table 2, the "CSP1" cell did not exhibit a sudden heating, highly exothermic event, until after the cell exceeded 200°C, reaching 218°C. In contrast, the "CCS1 on Anode" sample experienced a sudden heating, highly exothermic event, at 132°C. As shown in Table 2, the two cells with PE separator samples also experienced a sudden heating event near 132°C.

[0076] Example 4 The thermal conductivity of CSP films for use as separators produced by the above method was also tested in comparison with CCS and polymer sheets of corresponding dimensions. For the "CSP" thermal conductivity tests in this example, CSP version separators with two different treated boehmite as well as the CSP-A version were used. The advantage of eliminating the polymer substrate as in conventional CCS separators was confirmed by laser flash (transient) testing according to ASTM E1461 on 20 μm CSP separators ("CSP20") and PE polymer sheets. The ASTM E1461 method is accurate in providing quantitative and reproducible thermal conductivity measurements of thin separator samples. As reflected in Figure 15, the CSP separator showed a significant improvement in thermal conductivity at both 25°C and 50°C, with a thermal conductivity at 50°C that was approximately 10% higher than that at 25°C, approximately 0.6-0.7 W / m K compared to approximately 0.14-0.15 W / m K for the polymer sheet. The higher thermal conductivity of the separator is beneficial in faster diffusion of heat buildup within the cell, thereby reducing hot spot temperatures and improving safety in the event of a short circuit or other sudden heating event in one area of ​​the cell.

[0077] Example 5 Nail penetration safety tests were performed on lithium ion pouch cells incorporating the CSP film produced as described above as a separator in comparison to pouch cells incorporating a PE (polyethylene) polymer separator. Separate tests were performed on 3.5 Ah capacity cells and 75 Ah cells. For the "CSP" nail penetration safety tests in this example, pouch cells with CSP-A version separators were used.

[0078] Prior to testing, a high voltage 3.5 Ah pouch cell was charged to 4.4 V and a 3 mm diameter nail was driven through approximately the center of the cell at approximately 8.13 cm / sec. The results of the test are shown in Table 3 below.

[0079] [Table 3]

[0080] Prior to testing, the 75Ah pouch cell was charged to 4.1V and a 3mm diameter nail was driven through approximately the center of the cell at approximately 8cm / sec. The results of the test are shown in Table 4 below.

[0081] [Table 4]

[0082] As shown in both Tables 3 and 4, the CSP cells provide significantly improved mechanical and associated fire safety in nail penetration tests, with no fires observed in the CSP cells and peak temperatures below 100°C in both sets of tests. As cells get larger, such as the 40 Ah cells, and as cells use less safe electrode materials, such as 80:10:10 nickel manganese cobalt (811NMC) and high nickel cobalt aluminum (NCA) cathode materials and silicon anode materials, it becomes increasingly difficult to pass the nail penetration test with CSS, especially with PE separators. Since safety is the most important characteristic and absolute requirement in lithium-ion batteries, it would be very beneficial if the separator was thermally stable enough and thermally conductive, and could enhance the safety of the battery by itself compared to CCS and plastic separators. There are several other cell designs known to improve the safety of lithium-ion cells, but they are expensive and may not always be effective, so it would be very useful to be able to use a separator with superior safety characteristics. Thus, this testing reflects the improved safety of cells incorporating CSPs formed according to the invention in the manner described herein in preventing ignition events and maintaining below peak ignition temperatures even through induced mechanical failure, such as penetration of the separator and cell by a conductive metal during operation.

[0083] Figures 16A and 16B are graphical plots of temperature and voltage versus duration of the nail penetration test for the 3.5 Ah "control" PE cell and the CSP-A cell, respectively. As shown in these figures, the PE separator cell experienced a voltage drop after only 10 seconds, and the temperature rose to 700°C at one thermocouple on the surface of the cell and to about 580°C at a second thermocouple attached to the surface of the cell after nail penetration. These peak temperatures of 700°C and 580°C were reached in only 30-40 seconds after nail penetration. In contrast, as shown in FIG. 16B, the CSP-A cell only exhibited a slow linear voltage drop from 4.2V to 3.6V in the first 3100 seconds after nail penetration, and the peak temperature measured by thermocouples attached at two locations on the exterior surface of the cell began with a peak of about 50° C. and dropped to about 40° C. as the cell slowly discharged to 3.6V over the second 3100 second duration of the nail penetration test. Similar results are shown in FIGS. 16C and 16D, respectively, for the nail penetration test for the 5Ah pouch cells with PE separator (Control PE#1 in Table 6) and CSP-A separator (CSP-A 16 micron in Table 6). The 5Ah cell with the PE separator developed an immediate hard short with explosion and burning in less than 3 seconds. The 75Ah cell with the 16 micron thick CSP-A separator discharged slowly over about 5 minutes with no safety events.

[0084] Additional nail penetration tests were also conducted under modified conditions on the 5Ah CSP-A pouch cells, where the electrodes were NMC / graphite, the 5Ah CSP-A cells were configured with LiPF6 with an organic carbonate solvent system, and the tests were conducted at 100% state of charge (SOC) (4.2V). As the results in Table 5 below show, all CSP cells maintained a maximum temperature below 70°C.

[0085] [Table 5]

[0086] In another nail penetration test, 100% SOC 5Ah pouch cells with 16 micron and 20 micron CSP-A separators were tested with a 3mm diameter nail at a penetration rate of 2.5cm / sec versus a control polyolefin (PE) separator cell. As shown in Table 6 below, the CSP separator cells showed improved safety.

[0087] [Table 6]

[0088] In Table 6, an immediate hard short in the PE separator cell was indicated by a voltage drop to 0 volts and the cell exploding within about 3 seconds. This resulted in the immediate discharge of much of the cell's energy, which quickly heated the cell to a very high peak temperature as measured. A significant short in the CSP-A separator was indicated by a short that took about 5 minutes to an hour to completely discharge the cell to 0 volts. This fairly gradual energy discharge kept the peak temperature of the cell below 100°C. These results are reflected in Figures 16C and 16D for the nail penetration test of the 75 Ah pouch cell. One of the main reasons for this enhanced safety of the CSP of the present invention in the nail penetration test is the lack of shrinkage of the CSP (less than 1% shrinkage, typically less than 0.5%) at temperatures up to 600°C or higher. This lack of shrinkage prevents the hole in the separator caused by the nail penetration from expanding and exposing a larger area to the short circuit between the anode and cathode. When the local temperature around the nail reaches around 600°C, the thin aluminum metal current collector layer of the cathode melts at that temperature, but the CSP does not melt or shrink and maintains its electrical insulating properties around the nail hole, slowing the rate of forced short circuit discharge of the cell and the associated generation of high heat. As a result, the nail penetration test does not cause any safety event for the cell, i.e., the cell does not smoke, scorch, burn, or explode. In addition to safety and stability testing, cells with CSP-A separators made according to exemplary embodiments of the present invention as described above were also subjected to operational testing to ensure acceptable performance.

[0089] Example 6 Several 5 Ah pouch cells incorporating CSP separators with the CSP-A version separator were life cycle tested and showed comparable performance to the control polymer (polyolefin) (PE) separator cells. The "CSP" life cycle tests in this example used pouch cells with the CSP-A version separator.

[0090] As shown in Figure 17A, the 5 Ah pouch cells with 16 μm CSP separator performed comparably to the cells with 16 μm PE separator in a 3000 charge / discharge life cycle test at 1C charge / discharge at about 85% capacity retention. Figure 17B shows the life cycle test results of various CSP-A with different thicknesses, corresponding to the comparison with the PE separator in Figure 17A. As shown in these figures, all the CSP-A cells performed comparably to the PE cells.

[0091] Example 7 The rate capabilities of 5 Ah pouch cells incorporating various thicknesses of CSP-A separators were evaluated. In the "CSP" rate capability tests in this example, pouch cells with CSP-A version separators were used. As reflected in Figures 18A-18D, the cells with the 16 micron CSP separator outperformed the cells with the 22 micron CSP separator and the cells with the 16 micron PE separator ("control") up to 2C discharge rates (C-rates) at 0°C, 25°C, and 45°C. For example, the relative capacities for 2C cycling at 25°C for the 16 micron CSP cell and the 16 micron PE cell were 91% and 89%, respectively. As shown in this example, the CSP-A cell performed satisfactorily as well as the control PE cell.

[0092] Example 8 Various storage characteristics of cells incorporating CSP separators were evaluated. In a 28-day storage test, cells with a 20 micron CSP separator (CSP-A version) were compared to cells incorporating a 16 micron PE separator ("control"). As shown in FIG. 19A, the CSP separator cells exhibited improved capacity retention of about 96% over the control cells, which had a capacity retention of just under 95%, and retention consistency. Correspondingly, the CSP separator cells also exhibited more consistency in minimum voltage drop of about 70 mV for 28 days of storage at room temperature and 100% state of charge ("SOC"), as shown in FIG. 19B.

[0093] The CSP-separator (CSP-A version) cells were also tested for discharge capacity and voltage change over more than one year of storage at ambient conditions. The results are shown in Figures 20A and 20B. As shown in Figure 20A, the CSP-A separator cells retained their discharge capacity after one year of storage, as indicated by the discharge capacity measured by C / 3 discharge / charge cycling before and after one year of age. Also, as shown in Figure 20B, the CSP-A separator cells showed only about 30-40 mV voltage drop at 50% SOC after one year of storage, starting at about 3.7 V at 50% SOC.

[0094] Example 9 5 Ah pouch cells incorporating a 16 micron CSP separator (CSP-A version) were evaluated for discharge resistance against a 16 micron PE separator cell ("control") at 50% SOC using a 10 second pulse resistance method. Cells with CSP-A version separators were used in the discharge resistance tests in this example. As shown in Figures 21B and 21C, the CSP separator cells exhibited comparable discharge resistance to the control cells at 0°C. In the temperature range of 15°C to 45°C, the CSP-A separator cells exhibited slightly higher discharge resistance, as reflected in Figures 21A and 21C.

[0095] Example 10 Thermomechanical analysis (TMA) was performed on CCS, high density polyethylene (HDPE), and CSP separator (CSP-A version), respectively. Both CCS samples were single-sided ceramic coated PE (CCS1) and double-sided ceramic coated PE (CCS2). The CSP-A version separator was used for the TMA performed in this example. As shown in Figure 22. The CSP separator showed dimensional stability with no shrinkage up to 220°C, whereas the HDPE and CSS comparative samples all showed large dimensional changes of more than 20% at lower temperature ranges below 190°C.

[0096] VI. Vacuum drying (CSP-A) As mentioned above, according to an exemplary embodiment of the present invention, the CSP separator cell may be vacuum dried at an elevated temperature, for example in an unsealed pouch, prior to electrolyte filling to improve life cycle performance. In a preferred embodiment, the cell may be vacuum dried for about 1-4 hours at about 130° C.-150° C., or above 130° C., prior to electrolyte filling, so long as the temperature and time of heating do not damage or degrade the anode, cathode, pouch casing material, or any other components of the dried cell.

[0097] Example 11 Life cycle tests were performed on CSP separator cells that were not dried before electrolyte filling, vacuum dried, and stack dried. The life cycle tests performed in this example used cells incorporating the CSP-A version separator. As shown in Figure 23, the cells that were vacuum dried at 130°C for 4 hours showed a significant improvement in discharge capacity retention over about 200 1C charge / discharge 100% depth of discharge (DoD) cycles, and after 2000 1C charge / discharge 100% DoD cycles, the discharge capacity retention improved to 86% compared to 82% for the non-dried cells.

[0098] Also, as shown in Figures 23B and 23C, cells vacuum dried at 130°C for 4 hours before electrolyte filling (CSP-A version in pouch casing) exhibited improved discharge capacity for 1C / 1C charge / discharge cycling at both room temperature and 45°C versus laminated dried cells that were dried after stacking and before being placed in a cell casing or enclosure, e.g., a pouch, and improved cycle life of about 50% longer, as estimated from 92% capacity retention at 45°C for 500 cycles and 93% capacity retention at room temperature for 1000 cycles. This improvement in cycle life of the pouch vacuum dried cells compared to the laminated vacuum dried cells was confirmed by 2C / 2C charge / discharge cycling tests at room temperature and 45°C. The results are shown in Figures 23D and 23D. At room temperature, the pouch cells had 91% capacity retention after 500 cycles compared to 86% capacity retention for the laminated cells after 500 cycles. At 45° C., the pouch cell had 85% capacity retention after 500 cycles compared to 78% capacity retention for the laminated cell after 500 cycles.

[0099] Additional embodiments with CSP-B, CSP-B2, and CSP-B3 As discussed above, including in Table 1, all-ceramic free-standing separators may be formed by varying the ratio of each boehmite grade in the coating mixture. Separators from coating mixtures having the ratios of CSP-B, CSP-B2, and CSP-B3 discussed above were shown to exhibit suitable qualities for use in lithium-ion cells and were comparable to the results described herein for lithium-ion cells with CSP-A separators.

[0100] Example 12 Cycling rate capability tests were performed on CSP separator cells with CSP-A and CSP-B (above) versions of the separator, respectively. Figure 24 is a graph showing the improved cycling rate capability of the CSP-B separator cells over the CSP-A separator cells at higher discharge rates at 23°C up to a discharge rate of 20C. At a discharge rate of 10C, the CSP-A separator retained an average of 55% capacity, while the CSP-B separator retained an average of 73% capacity.

[0101] Correspondingly, cold crank amp (CCA) measurement tests were performed on CSP separator cells with CSP-A and CSP-B (above) versions of the separator, respectively. FIG. 25 is a graph plot showing the improved results of the CSP-B separator cells over the CSP-A separator cells. As shown in FIG. 24 and reflected in more detail in FIGS. 33C and 33D below, the CSP-B (and especially CSP-B2) separators, which have larger average particle size, higher air permeability, and higher porosity, exhibited lower impedance and improved capacity retention at high rates when compared to the CSP-A separator.

[0102] VII. Vacuum drying (CSP-B2) As mentioned above, according to an exemplary embodiment of the present invention, the CSP separator cell may be vacuum dried at an elevated temperature, for example in an unsealed pouch, prior to electrolyte filling to improve life cycle performance. In an exemplary embodiment, the free-standing CSP separator, or its precursor in roll form, may also be vacuum dried prior to cell fabrication to improve mechanical properties. Vacuum drying at elevated temperatures affects the crystallinity and thus the resulting mechanical properties. The vacuum conditions are important for the removal of moisture and possibly other volatiles such as residual NMP and p-TSA. The initial coating and drying process may also provide annealing of the PVdF binder in the presence of boehmite or other ceramic particles, which is expected to result in enhanced mechanical properties during cell fabrication.

[0103] In a preferred embodiment, the separator (eg, films 415a and 415b described above) may be vacuum dried at about 130° C. to 150° C. for about 1 hour to 4 hours.

[0104] Example 13 20 micron CSP-B2 samples were tested for mechanical properties before and after vacuum drying in roll form. Figure 26A shows the respective machine direction (MD) tensile curves of such samples before and after vacuum drying at 130°C for 4 hours. The results of selected parameters are summarized in Table 7 below.

[0105] [Table 7]

[0106] As reflected in FIG. 26A and Table 7 above, the physical properties of the CSP samples were improved by vacuum drying in the finished roll form. The maximum tensile stress increased, the fracture energy / toughness increased, the Gurley air permeability number decreased, and swelling in propylene carbonate (PC) decreased. The tensile stress number was about 10% higher for the vacuum dried CSP-B2 compared to the non-dried CSP-B2 separator. Swelling measurements in PC are made by immersing a 10×10 cm separator piece in PC on a flat glass plate and measuring the MD and CD % swelling on both edges after 1 hour of immersion and averaging the four results. Immersion in PC provides an estimate of the % swelling when immersed in an organic electrolyte containing an organic carbonate solvent and a lithium salt at a concentration of about 15% by weight. Excessive swelling of the separator, such as swelling greater than 5% when wetted with an organic electrolyte, is undesirable and can cause yield and quality problems in cell manufacturing. These results for the CSP-B2 separator confirm improved mechanical and electrolyte swelling properties to better withstand stress and improved separator alignment requirements associated with the cell manufacturing process.

[0107] Example 14 Additional mechanical testing was performed on CSP-B2, CSP-B3, and other films with the same blend ratio of boehmite particles and various pigment:binder ratios and separator thicknesses before and after vacuum drying, as summarized below in Table 8. The results are shown in Figures 26B-26D.

[0108] [Table 8]

[0109] As shown in Figures 26B and 26C, all samples exhibited higher ultimate tensile loads for 0.75 inch wide separator samples, and exhibited approximately 20%-30% higher ultimate tensile stresses to values ​​in the range of 2300-3000 psi after vacuum drying (VD) compared to the initial pre-drying state (initial). This is a significant advantage for the mechanical strength of the CSP. As shown in Figure 26D, some samples exhibited a slight decrease in elongation at break (%) after vacuum drying, but still had elongation within the acceptable range of more than 15%, typically 25%-40%, after vacuum drying.

[0110] Example 15 Additional mechanical tests were performed on the CSP-B2 and CSP-B3 samples under various parameters before and after vacuum drying. FIG. 26E shows the equivalent weight of such samples in the same area before and after vacuum drying at 130° C. for 3 hours, 150° C. for 1 hour, and 150° C. for 3 hours, respectively. The CSP-B2 sample (or “G2r2”) showed a slight increase in equivalent weight after vacuum drying at the higher temperature, while the CSP-B3 sample (or “G2r3”) also showed a slight increase in weight after vacuum drying. These weight changes are very small and within the experimental error, as shown by the standard deviation bar for each bar of data in FIG. 26E. FIG. 26F shows the thickness of the samples before and after vacuum drying. As shown in FIG. 26F, the CSP-B2 sample showed a slight decrease in thickness after the short 1-hour vacuum drying period, and the thickness returned to nearly the initial state after the longer 3-hour drying. Correspondingly, the CSP-B3 sample showed a slight decrease in thickness after vacuum drying at the higher temperature. These changes in thickness, as measured by a Dorsey gauge, are very small and within the experimental error, as shown by the standard deviation bars for each bar of data in FIG. 26F. Finally, FIG. 26G shows the Gurley air permeabilities of the samples, which did not show any significant change after vacuum drying. FIG. 26G shows that CSP-B3 (or "G2r3"), which has a Gurley number of about 280 sec / 100 cc air, has a significantly lower air permeability number and greater air permeability or porosity than CSP-B2 (or "G2r2"), which has a Gurley number of about 600 sec / 100 cc air.

[0111] VIII. Calendaring According to an exemplary embodiment of the invention, the films 415a and 415b described above with reference to Figure 4 may be subjected to calendering prior to cell fabrication to reduce their thickness while maintaining acceptable mechanical and electrical properties for use in lithium ion cells. In an exemplary embodiment, the films 415a and 415b may be calendered between upper and lower rolls against a polymer (e.g., PET) film substrate.

[0112] Example 16 Samples of CSP-A, CSP-B2, and CSP-B3 films were prepared as described above and cut prior to peeling to provide sheets up to about 12 inches wide and about 18-24 inches long with the CSP layer remaining on the PET peel substrate, and calendered with a heated bottom roll.

[0113] The samples were calendered in different configurations: "Up" means that the CSP side was facing the top unheated roll, and the PET film side was facing the heated bottom roll, which is the opposite, "Down".

[0114] Initial experiments were conducted at a pressure of about 1500 psi (or about 1250 pounds per linear inch) with the bottom roll heated to about 110°F to about 140°F.

[0115] Sample (1) was 20 micron CSP-B2, 3.75 pigment binder (P:B). Samples (1), (1)A, and (1)B were calendered in the "up" direction for one pass. The starting 20 micron CSP became more transparent with calendering to a thickness of about 13-15 microns, which is about a 30% reduction in thickness. Sample (1)C was passed through the calender twice, with the second pass in the opposite direction. The thickness did not appear to change significantly with the second calendering pass. Due to non-uniformity in the calendering pressure across the width of the sheet, the clearing of these samples was not uniform, with one side being more transparent and the sample having areas that were partly transparent and partly slightly opaque.

[0116] Samples (1)D and (1)E had 20 microns of CSP-B2 and were run in the "down" orientation. The thickness reduction was small compared to the "up" orientation, only reducing the thickness to 16-17 microns. Sample (1)F had two passes, but this did not appear to further reduce the thickness of the CSP-B2.

[0117] Sample (2) had a CSP-B3 of 20 microns, P:B of 4.25:1. Samples (2) and (2)A were run in the "up" position resulting in a CSP thickness of approximately 16-17 microns. Sample (2)B had no significant change in thickness over two passes. Samples (2)C and (2)D were calendered in the "down" position resulting in a CSP thickness of approximately 17-18 microns. Sample 2(E) had no significant change in thickness over two passes.

[0118] Sample (3) had a CSP-B2 of 12 microns (labeled as 10 microns in Table 9), P:B of 3.75:1. Samples (3) and (3)A were run "up" resulting in a CSP thickness of approximately 10 microns. Sample (3)B did not change significantly in thickness over two passes. Unlike the 20 micron CSP, there was some "pickoff" of the 12 micron thick CSP coating in places due to the calendaring operation. This was believed to be due to wear and tear of the thinner CSP rather than adhesion of the CSP layer to the calendar rolls. Sample (3)B did not change significantly in thickness over two passes. Thickness change was unchanged for Samples (3)C and 3(D) in one pass and for Sample (3)E in two passes.

[0119] Sample (4) was CSP-A, 3.75P:B with a thickness of about 26-27 microns. Sample (4) was calendered in the "up" orientation to a thickness of about 20-21 microns.

[0120] Sample (4)A was calendered in the "down" orientation to a thickness of approximately 20-21 microns.

[0121] The next calendering run was done at 750 psi, which is about 700 pli (pounds per linear inch). This did not result in much clearing. Sample (1)G was calendered in the "up" position, resulting in a CSP thickness of 16 microns. Sample (1)H was calendered in the "down" position. Samples (2)F and (2)G were calendered in the "up" and "down" positions, respectively. Samples (3)F and (3)G were calendered in the "up" and "down" positions, respectively. Samples (4)B and (4)C were calendered in the "up" and "down" positions, respectively.

[0122] The calender was then set to 250°F (its maximum setting) for "hot" calendering. The temperature reading was about 280°F. This temperature was too high to calender the base PET film without distorting it. The following samples were run: Samples (1)l and (1)J were calendered in the "up" direction for one pass, resulting in a CSP thickness of about 14-15 microns. Sample (1)K did not show a significant change in thickness over two passes. Other samples were run, but all had some distortion of the PET substrate. This indicates that the calender roll temperature was set too high for this set of experiments.

[0123] The above mentioned calendaring conditions are summarized in Table 9 below.

[0124] [Table 9]

[0125] Samples (1, 1A, 1B, 1C(2x), and 1G) and (2G) in Table 9 were tested for mechanical properties and air permeability (Gurley). The results are reflected in Figures 27A-27E. As shown in Figure 27A, Samples (1, 1A, 1B, and 1C(2x)) (CSP-B2 or "G2r2" PC3.75) exhibited a maximum tensile stress (≈2200 psi) that was approximately 10% greater than the control sample, which was the uncalendered sample shown at the far left of Figures 27A-27D. Also, as shown in Figure 27A, Sample 2G (CSP-B3 or "G2r3" PC4.25) exhibited a maximum tensile stress of approximately 2000 psi that was approximately 20% greater than the control sample, which was the uncalendered sample shown second from the left of Figures 27A-D. Both samples (1B) and (2G) (CSP-B3 or "G2r3" PC4.25) exhibited maximum tensile loads (≈0.5-0.55 kg) comparable to the 0.75 inch wide samples, as shown in FIG. 27B. It is important to note here that the calendered samples are approximately 5%-30% thinner, thus offering the significant advantage of reduced thickness while still providing comparable tensile loads to the uncalendered samples. As shown in FIG. 27C, samples (1, 1A, 1B, 1C (2x), and 1G) had elongations at break of approximately 25%-40% compared to the control uncalendered CSP-B2, which had a % elongation of approximately 40%. These results indicate that the elongation and flexibility of CSP-B2 is not significantly reduced by calendering. As shown in FIG. 27C, CSP-B3 sample 2G had an elongation at break of approximately 15%, which is comparable to the elongation of the control uncalendered CSP-B3 sample. Both samples (1, 1A, 1B, 1C (2x), and 1G) and (2G) exhibited relatively high Gurley air permeability numbers compared to the control sample. FIG. 27D shows the relative Gurley air permeability numbers between the CSP samples in more detail. These higher Gurley air permeability numbers after high levels of calendaring are not expected to result in a corresponding decrease in ionic conductivity due to the electrolyte swelling the CSP to its original pre-calendering state.These calendering results show that calendering provides another useful option for optimizing the tradeoff between higher mechanical strength and higher % porosity of the separator. For example, CSP-B3 has lower mechanical strength and higher porosity than CSP-B2, but CSP-B3 (or versions with higher pigment:binder ratios but lower mechanical strength) can be made mechanically stronger by calendering while maintaining good porosity and ionic conductivity.

[0126] FIG. 27E shows the Gurley air permeability versus progressive compressions for various CSP-A (20 micron thick), CSP-B2 (12 and 20 micron thick), and CSP-B3 (20 micron thick) samples. As shown in FIG. 27E, at 10% compression with calendaring, the Gurley number of CSP-A was about 8 times higher than the value before calendaring. For the 20 micron thick samples of CSP-B2 and CSP-B3 at 10% compression, the increase in Gurley number upon calendaring was about 1.5 times or less. This supports the evidence that the higher porosity and lower Gurley number CSP-B2 and CSP-B3 separator designs with blends of large and smaller grade boehmite particles are better than the CSP-A separator design in terms of mechanical strength through calendaring and providing edge reinforcement and strength by compressing the edge regions of the separator.

[0127] IX.Crosslinking According to an exemplary embodiment of the present invention, a cross-linking coating material may be applied to the CSP films, such as films 415a and 415b described above, prior to cell fabrication to enhance the mechanical properties of the resulting separator. The cross-linking coating may be a polyaziridine cross-linker, an isocyanate cross-linker, or the like.

[0128] Example 17 Samples of CSP films (CSP-A and CSP-B2) with difunctional and trifunctional isocyanate crosslinkers incorporated into the coating mixtures of CSP-A and CSP-B2 were tested for mechanical properties.

[0129] The baseline formulation (CSP-A version) used CSP 3.5:1 with Solef® 5130 and utilized Teracure® N33 (Desmodur® N3300) (trifunctional) and Desmodur® W (difunctional) at loadings of 0.375 phr (per hundred parts resin) and 0.75 phr, respectively.

[0130] The sample was peel-coated SR. 2 / SKC Skyroll(registered trademark) SH-400 PET(SR 2 The sections were coated onto a SKC Skyrol® SH-400 PET liner substrate with a target dry coat thickness of 20 microns. Drying conditions were 400° F. for approximately 2 minutes and a line speed of 5.5 fpm (feet per minute). A portion of each section was made two passes through the coater under the same drying conditions.

[0131] Figures 28A-28D show the maximum tensile stress (Figure 28A), % elongation at break (Figure 28B), "toughness" (Figure 28C), and Gurley air permeability (Figure 28D), respectively, for crosslinker coated samples, as well as the results for samples coated with a trifunctional isocyanate crosslinker with its corresponding crosslinker molecule shown on the left side of the figures, and the results for samples coated with a difunctional isocyanate crosslinker with its corresponding crosslinker molecule shown on the right side of the figures. "Toughness", the energy per unit volume required to cause breakage, shown in Figure 28C, is represented by the integrated area under the stress-strain curve for each sample. Figures 28A-28D show the results for samples with crosslinker level / coater pass number (1 or 2) on their respective x-axes. As shown in Figure 28A, the trifunctional crosslinker, both at additive level and after one or two passes, did not result in a significant change to the tensile stress value of about 1500 psi when run through the coater oven without crosslinker for one or two passes. In contrast, the difunctional crosslinker increased the tensile stress value to about 1600 psi when run through the coater oven for two passes at the lower additive level or one pass at twice the additive level. The tensile stress value further increased to about 1720 psi by running through the coater oven for two passes at twice the additive level.

[0132] As shown in Figures 28A-28D (left side), the trifunctional crosslinker (Desmodur® N3300) samples did not show a significant increase in tensile strength, and elongation / ductility decreased with crosslinker loading. Correspondingly, the difunctional crosslinker samples showed a more pronounced increase in tensile strength with crosslinker loading, and a decrease in elongation with loading to a lower level. Furthermore, additional heating (second pass through the coater) clearly increased the elongation / toughness in those sections with the difunctional crosslinker. For example, the % elongation at break with 0.75 phr crosslinker and two passes through the coater oven was about 25%, unchanged from the control CSP-B2 without crosslinker. Additionally, crosslinker loading and additional drying had minimal effect on the Gurley air permeability values ​​for either crosslinker.

[0133] These results imply that the mechanical properties of the standard CSP separator, i.e., a CSP separator with a pigment-binder (P:B) ratio of 3.5:1 without a crosslinker, are comparable to those using a pigment:binder ratio of 4.0:1 with a bifunctional crosslinker, while also achieving a much lower Gurley value and, possibly, a higher porosity.

[0134] Example 18 Also prepared for testing were CSP-B2 (or "G2r2") samples coated with Desmodur® RE series crosslinker of the following formula: [ka]

[0135] Figures 29A-29C show the mechanical testing results of the samples. As shown in Figures 29A and 29B, over the range from 0 phr on PVdF binder to 6 phr of PVdF binder, the samples showed a monotonic increase in the initial tensile strength of the resulting films. Figure 29B shows that the tensile stress of CSP-B2 (or "G2r2") was approximately 130 kg / cm 2 Approximately 145kg / cm at 2phr loading of crosslinker 2 Up to approx. 150kg / cm at 4 phr loading of crosslinker 2 Up to approx. 160kg / cm at 6phr loading of crosslinker 2 On the other hand, Figure 29C shows a maximum elongation to failure of about 32% at 2 phr loading, implying loading as a factor in optimizing "toughness" i.e. the combination of tensile stress and ductility / elongation to failure as discussed above.

[0136] The decrease in ductility may be associated with increased brittleness of the system with higher loading of RE crosslinker (common in crosslinking polymers) or introduction of additional "point defects", e.g., gel or boehmite aggregates. At the same time, as shown in Figure 29C, the % elongation at 6 phr load of about 18% is only slightly lower than the % elongation at break of 24% for CSP-B2 without crosslinker, and the 4 phr load also shows no significant difference at about 24%.

[0137] Example 19 CSP-A samples coated with polyaziridine crosslinker (PZ-33-pentaerythritol tris(3-(1-aziridinyl)propionate) or PZ-28-trimethylolpropane tris(2-methyl-1-aziridinepropionate)) were prepared and mechanical properties were tested. The results are shown in Figures 30A-30C. As shown in these figures, the samples showed improvement in "toughness" with minimal impact on Gurley air permeability values. The addition of polyaziridine crosslinker at 0.5 phr and 1 phr increased the tensile stress of the CSP-A separator without crosslinker from 1540 psi to 1650 psi and 1700 psi, respectively, as shown in Figure 30A, and also increased the elongation at break of the CSP-A separator without crosslinker from 20% to 34% and 38%, respectively, as shown in Figure 30B.

[0138] X. Edge reinforcement According to an exemplary embodiment of the present invention, to reinforce the edges of the CSP film, such as the above-mentioned films 415a and 415b, and improve tear resistance and mechanical strength properties, an edge reinforcement coating may be applied to the CSP film in the narrow lane where subsequent slitting is to be performed to provide a CSP roll at the desired width, or after the CSP has been slit to size and prior to cell fabrication. The edge coating may be a UV cured material, a chemically crosslinked material, a strong and flexible polymeric material, etc. For additional tear resistance and mechanical strength, this edge coating may be combined with compression of the CSP at the edge region either before or after slitting.

[0139] Example 20 A polyethylene glycol diacrylate / pentaerythritol tetraacrylate (72:25) blend was applied to the "standard" CSP-A samples with various solid MEK (methyl ethyl ketone) solutions at various coating weights using a #3 Mayer rod. For testing purposes, the samples were coated at full coverage rather than coating in narrow lanes to provide edge reinforcement lanes after slitting. The oligomer / monomer blend was applied as a solution from MEK, but the coating may be applied at 100% NV. The MEK solution was used in this experiment to ensure control of coating weight and substrate wetting. The coatings were dried in an oven at 100°C for 60 seconds to remove the MEK. The resulting coated separators were then subjected to one pass through a Fusion UV system (H bulb, 20 ipm). From each coated sample, 100 cm 2 One sample was taken and the basis weight (mass / area) and thickness (4X / sample) were measured.

[0140] Figures 31A and 31B show the basis weight and thickness versus coating solids (%NV) for the samples, respectively. As expected, as the coating solids increased, the basis weight also increased by up to 8 grams per square meter (gsm), as shown in Figure 31A. However, as shown in Figure 31B, over the range of formulations used (using a #3 rod for deposition), the thickness did not increase with the coating solids. This implies that the coating was absorbed into the separator pores as desired. In other words, the tests showed that it would be feasible to improve the tear resistance and mechanical strength properties of the separator edges without significantly affecting the separator thickness profile. If the thickness at the edges were to increase due to stacking more material on the edges, the ability to wind up long slit separator rolls of 500 meters or more without stacking and becoming thicker and potentially cracking and resulting in damaged edges would be adversely affected.

[0141] Example 21 Additional testing of edge reinforcement coatings was performed by coating a radiation curable formulation (PEGDA / ethoxylated TMPTA, 75:25, various %V [20%-40%] in MEK) at full coverage onto a "standard" CSP-A (P:B=3.5:1, 20 micron) sample. The sample was then heat dried (120 sec @ 110°C) and UV cured (fusion unit, one pass at 20 ipm).

[0142] As shown in Figure 31C corresponding to Figure 31B, thickness did not increase with coat weight, implying that the UV cured coating was absorbed into the pores and UV cured within the pores. Also, thickness measurements at higher coat weights showed a slight decrease in thickness from about 19.5 microns to 19.0 microns at 6 gsm, suggesting a slight "densification" of the separator, possibly due to chemical shrinkage upon polymerization.

[0143] FIG. 31D shows that the Gurley air permeability values ​​increased significantly with increasing coat weight, but this increase did not become significant until coatings above 2 gsm. Since the narrow lanes of reinforced edges, such as 2-4 microns, on one or both edges of the separator are entirely or mostly outside the cell's active electrode and electrolyte laminate, the edge reinforcement areas do not need to be porous to allow lithium ions to diffuse through them during cycling. Thus, cell performance is acceptable if these areas of the separator are completely filled with strong reinforcing material, and in fact, since these edge areas are often freestanding at the edges of the cell laminate and are exposed to stresses from the casing and during cell assembly, they desirably need to be as strong and flexible as possible. FIG. 31E shows that the tensile stress at break decreased slightly with increasing reinforcing coat weight, but as reflected in FIG. 31F, the addition of reinforcing chemicals dramatically improved elasticity, from about 10% elongation at break to a maximum of about 30% at a fairly low attachment level of 1.5 phr. Figure 31G shows the unnotched tear resistance of 16 micron CSP-A samples with ("NP16 Saturated") and without ("NP16") edge reinforcement coatings of about 2.3 mN / micron and about 2.1 mN / micron, respectively. As shown in Figure 31G, the coated samples showed a significant improvement in tear resistance.

[0144] A very important point to note here is that the edge reinforcement layers of the CSP only need to be about 2-4 mm wide, and therefore these edges will be outside the electrode area since the separator is wider than the electrodes of a Li-ion battery to protect against short circuits in the absence of a highly insulating separator. Therefore, if these edge areas of the CSP are partially or completely filled with reinforcement material for additional mechanical strength, there will be no or little impact on the energy capacity and cycling of the cell. It is also important that these edges are not thicker than the rest of the CSP, as this would be problematic when winding up slit rolls of CSP, which can be up to 2,000 meters long in some cases. The above results show that the edge reinforcement material can be absorbed into the highly porous CSP layer without increasing thickness on the edges.

[0145] XI. Non-swelling layer As mentioned above, PVdF may be used as a binder material to form a free-standing CSP separator. One of the desirable features of PVdF is its stability up to 5V in lithium-ion and lithium-metal cells. However, very high molecular weight PVdF, such as Solef® 5140, swells by about 20% to 50% in electrolyte solvents, which may be advantageous for electrolyte wetting and impedance reduction, but may result in excessive swelling of the CSP separator. The inorganic materials in the CSP reduce the swelling of PVdF to some extent. To avoid excessive swelling of inorganic / organic composite separators in electrochemical cells, where the organic polymer and separator may swell by several percent in the presence of organic electrolyte, one or more non-swelling porous layers may be added to the composite separator to reduce the swelling to an acceptable level. This multi-layer approach also has the advantage of (1) reducing the possibility of pinholes by going from a single separator layer to multiple separator layers that are less susceptible to pinholes, and (2) providing non-swelling layers that may have other useful properties such as safety shutdown, inhibition of migration of transition metal ions, and increased mechanical strength. One or more of the non-swelling layers may be formed by inorganic oxides, inorganic nitrides, etc., and may comprise a polymer that may be insoluble in water or other solvents such as propylene carbonate, such as polyvinyl alcohol (PVA), which is insoluble in propylene carbonate and does not swell in propylene carbonate. As another example, the polymer may comprise water-insoluble polymer latex particles with a diameter of about 150 nm, such as products under the trade names Lumiflon® and Joncryl®. As mentioned above, one or more layers of the CSP separator may comprise a crosslinking agent that reacts with the polymer particles.

[0146] In an exemplary embodiment, one or more non-swelling layers may be between the inorganic / organic composite layers on either side, i.e., a "sandwich" configuration. The advantage of this is that it protects the intermediate non-swelling layer from direct interaction with the surface of one of the electrodes, providing better consistency and long-term performance in the cell. Other configurations may be used to incorporate one or more non-swelling layers, such as: (1) may incorporate one non-swelling layer and one PVdF swelling layer; (2) A non-swelling layer may be provided on each side of the PVdF swelling layer, (3) There may be two CSP layers laminated together with a non-swelling layer in the middle; (4) Edge reinforcement lanes may be added to configurations (1), (2), and (3) above by providing additional compression or calendaring to the lanes along which the separator will later be slit.

[0147] In an exemplary embodiment of the invention, a CSP separator incorporating one or more non-swelling layers as described above may have reduced swelling of about 3% to 4%, or preferably less than 1% to 2%, or more preferably less than 0.5%, when immersed in propylene carbonate or organic electrolyte for 1 hour. While the swelling tolerance may be increased for cylindrical or metallic prismatic cells where the separator is highly constrained within a metal case when electrolyte is added, the benefit of reduced swelling may be more pronounced for pouch cells where the case is a metallized plastic.

[0148] Example 22 Non-swelling microporous layer samples were formed by non-solvent induced phase inversion of polyamide (Elvamide® 8063) / polyvinyl butyral (Butvar® B-98) blends. 7 micron thick non-swelling layers of the various blends were laminated between two 3.5 micron thick layers of CSP-B2.

[0149] FIG. 32A shows a cross-sectional view of the layer structure of a non-swelling porous layer and a CSP-B2 ("CSP") layer, the CSP layer on either side of a separator with a non-swelling porous layer in the center. FIG. 32B is a graph showing the relationship between the Gurley air permeability value of the resulting laminate samples and the weight fraction of the non-swelling layer blend. Correspondingly, FIG. 32C is a graph showing the relationship between the % swelling ratio of the laminate samples and the weight fraction of the non-swelling layer blend. Low Gurley values ​​are maintained up to a weight fraction of 0.7 of E-8063 polyamide in the non-swelling polymer blend. As shown in these figures, the non-swelling layer made by the phase inversion method was effective in reducing swelling in propylene carbonate, a representative solvent for non-aqueous electrolytes, resulting in a Gurley air permeability value slightly below 200 sec / 100 cc.

[0150] Example 23 Samples with the corresponding CSP-non-swelling layer-CSP structure were tested separately for swelling. An approximately 16 micron thick polyvinyl alcohol (PVA)-boehmite layer with 11 parts ethylene carbonate, 6 parts divinyl ether of triethylene glycol (DVE-3), and 3 parts polyethylene oxide (molecular weight 200), made according to paragraph 4 of Example 1 of U.S. Patent No. 8,883,354 to Carlson, et al., served as a non-swelling layer laminated between two CSP-B2 layers with a thickness of approximately 11 microns.

[0151] The resulting properties of the laminates are summarized in Table 10 below.

[0152] [Table 10]

[0153] As shown in Table 10 above, the laminate showed less than 0.5% swelling after immersion in propylene carbonate for 1 hour. Thus, the effectiveness of laminating a solvent swellable, yet strong and flexible, highly stable and safe CSP version at high temperatures in lithium ion batteries to a non-swellable, yet less elongated layer to reduce net swelling was confirmed. Although the samples exhibited a net reduction in tensile strength and reduced elongation / ductility compared to the CSP-B2 separator, this could be improved by tailoring the composition of the non-swellable layer for better elongation / ductility to better match the higher elongation before break of the solvent swellable, highly safe CSP version as described here for CSP-A, CSP-B, CSP-B2, and CSP-B3 with flame retardant PVdF polymer binder. The net effect on Gurley air permeability values ​​was negligible (once normalized to 20 microns).

[0154] Example 24 Separator samples made according to the CSP-B blend ratio and the CSP-B2 blend ratio were evaluated against samples made with the CSP-A coating mixture blend ratio.

[0155] 33A shows the ultimate tensile strength (psi) results for samples of the three separator versions CSP-A, CSP-B, and CSP-B2. As shown in FIG. 33A, the CSP-B2 sample, despite using less binder (P:B of 3.75:1 for CSP-B2 vs. 3.5:1 for CSP-A), provided about a 10% increase in mechanical strength at 2000 Psi compared to CSP-A, while exhibiting an acceptable tradeoff relative to the CSP-B version when considering the balance of other properties, as detailed below.

[0156] Figure 33B shows the % elongation at break for samples of the three separator versions CSP-A, CSP-B, and CSP-B2. As shown in Figure 33B, the CSP-B2 sample exhibited slightly lower elongation of about 25% compared to SP-A with an elongation of about 30%.

[0157] 33C and 33D show the Gurley air permeability numbers and separator impedance of samples of the three separator versions CSP-A, CSP-B, and CSP-B2, respectively.

[0158] The CSP-B2 separator showed a significant reduction in Gurley air permeability to about 550 sec / 100cc compared to 1050 sec / 100cc for CSP-A and 900 sec / 100cc for CSP-B while maintaining mechanical strength very close to that of the CSP-B separator. The CSP-B separator showed a substantial improvement in mechanical strength compared to CSP-A as reflected in Figures 33A and 33B, while exhibiting a higher impedance as shown in Figure 33D, despite having a slightly lower Gurley air permeability number. As a result, the CSP-B2 sample provided a desirable improvement in separator impedance, lowering it by about 25% from that of CSP-A, along with a significantly larger reduction in the Gurley value (Figure 33C), while maintaining mechanical properties within acceptable ranges.

[0159] Figure 33E shows the linear dimensional change (swelling properties) of the samples of the three separator versions CSP-A, CSP-B, and CSP-B2. As shown in Figure 33E, the CSP-B sample showed a significant reduction in separator swelling to about 3.3% in propylene carbonate compared to CSP-A with a % swelling of about 6.5%. Correspondingly, the CSP-B2 version with larger pore size and less PVdF binder showed further improvement with a slightly lower swelling of about 3.0% compared to CSP-B.

[0160] As shown above, the CSP-B2 blend resulted in a separator with improved mechanical strength of about 2,000 psi while significantly reducing the Gurley value, separator impedance, and swelling properties over the CSP-A separator. A summary of the results is further shown in Table 11 below.

[0161] [Table 11]

[0162] XII.Extraction As mentioned above, one or more ceramic components in the coating mixture blend may be surface treated, for example with p-toluenesulfonic acid, to facilitate dispersion in organic solvents instead of using dispersants that can result in low molecular weight species and potentially migratory components that can degrade cell performance. Furthermore, as mentioned above, applying crosslinkers, i.e., adding low molecular weight additives that cannot be fully "bonded" to the main separator components (such as boehmite and PVdF binder) by chemical bonds, is one of many options for further improving the mechanical and / or electrochemical properties of CSPs.

[0163] As further explained above, Desmodur® RE is an example of a crosslinker that, in testing, demonstrated improved mechanical properties at loading levels of about 1%-6% w / w PVdF polymer binder in CSP separators (i.e., very low overall loadings). In this example, the resulting separator coating is a characteristic pink-purple color (depending on crosslinker loading and exposure to light). One cause for concern is that this characteristic color easily leaches out of the separator when exposed to electrolyte solvents. Thus, extraction testing was performed to confirm the maintenance of beneficial mechanical properties when exposed to solvents.

[0164] Example 25 Extraction of the modified CSP-A dried separator (D10SR / D10F4 50:50, S5140, 2% RE) with aqueous alcohol was performed in a water / IPA (50:50) bath for 60 min. The extracted samples and control samples were then dried at 100 °C for 60 min.

[0165] FIG. 34A is a photograph showing the different coloration between the crosslinked “pristine” and “extracted” samples, indicating that the water / alcohol extraction removes most of the “color” from the RE modified CSP coating.

[0166] Figure 34B is a graph of a representative tensile curve for each sample, reflecting the slight improvement in tensile strength due to extraction. These results are confirmed by the maximum tensile load and stress shown in Figures 34C and 34D.

[0167] The elongation / ductility did not change after extraction, as shown in Figure 34E, while the Gurley values ​​showed a small but statistically significant decrease, as shown in Figure 34F.

[0168] In summary, a free-standing CSP separator is provided with improved safety, thermal stability, and heat transfer properties compared to CCS separators. The added thermal stability of the CSP of the present invention allows for high temperature vacuum drying, such as 130°C to 150°C, of ​​the CSP, cell stack of electrodes with the CSP, and dried cells with the CSP, which is not possible with CCS. This high temperature vacuum drying results in improved cell cycle life, rate capability, and storage stability of the cell. Most importantly, the CSP shows superior safety results compared to CCS when tested in cells by ARC and nail penetration test methods.

[0169] The free-standing CSP separator of the present invention has improved performance over conventional CSP separators, especially in higher mechanical strength, while providing excellent elongation / ductility and higher ionic conductivity and rate capability. Many process and material options are described herein to obtain the improved performance of the CSP separator of the present invention, including, but not limited to, the use of specific blends of ceramic particles and mixing and filtration processes for CSP coating with these blends, the use of functionalized PVdF such as Solef® 5130 and Solef® 5140 with preferred functionality and molecular weight, the use of different non-swelling porous layers to reduce swelling of the CSP in the electrolyte, vacuum drying at high temperatures for both the CSP and the dried cell with the CSP, the use of edge reinforcement materials on the slit edges, the use of crosslinking agents in the CSP layer, the use of a calendaring process for the CSP, the use of solvent / water extraction to remove soluble materials, the addition of a shutdown layer, and combinations thereof.

[0170] Since various embodiments of the present invention have been shown and described in detail above, various modifications and improvements thereon should be readily apparent to those skilled in the art. Therefore, the spirit and scope of the present invention should be broadly construed without being limited by the specification.

Claims

1. 1. An electrochemical cell comprising: an anode material disposed on an anode current collector; a cathode material disposed on a cathode current collector; a separator assembly disposed between the anode material and the cathode material, the separator assembly including a first separator layer, a second separator layer, and an intermediate layer disposed between the first separator layer and the second separator layer, the intermediate layer configured to prevent further operation of the electrochemical cell when a trigger condition is met. Electrochemical cell.

2. the trigger condition includes the intermediate layer exceeding a threshold temperature; 2. The electrochemical cell of claim 1.

3. At least one of the first separator layer or the second separator layer includes a ceramic layer.

2. The electrochemical cell of claim 1.

4. The ceramic layer comprises a ceramic powder.

4. The electrochemical cell of claim 3.

5. At least one of the first separator layer or the second separator layer comprises a porous polymer.

2. The electrochemical cell of claim 1.

6. the intermediate layer comprises a soluble particulate filler material; 2. The electrochemical cell of claim 1.

7. At least one of the first separator layer or the second separator layer comprises polyvinylidene fluoride (PVdF); 2. The electrochemical cell of claim 1.

8. At least one of the first separator layer or the second separator layer has a thickness of less than 20 μm.

2. The electrochemical cell of claim 1.

9. The electrochemical cell reaches a peak temperature of 100° C. or less in a nail penetration test in which a nail having a diameter of 3 mm is penetrated at 80 mm / s.

2. The electrochemical cell of claim 1.

10. At least one of the first separator layer or the second separator layer comprises boehmite particles; 2. The electrochemical cell of claim 1.

11. 1. An electrochemical separator assembly comprising: a first separator layer comprising a porous polymer material; a second separator layer comprising a ceramic material; an intermediate layer disposed between the first separator layer and the second separator layer, the intermediate layer configured to pass an electroactive species when a trigger condition is met. Electrochemical separator assembly.

12. The ceramic material comprises a ceramic powder. The electrochemical separator assembly of claim 11.

13. the second separator layer comprises boehmite; The electrochemical separator assembly of claim 11.

14. At least one of the first separator layer or the second separator layer has a thickness of less than 20 μm. The electrochemical separator assembly of claim 11.

15. the porous polymer material comprises polyethylene; The electrochemical separator assembly of claim 11.

16. At least one of the first separator layer or the second separator layer comprises polyvinylidene fluoride (PVdF); The electrochemical separator assembly of claim 11.

17. the intermediate layer comprises a soluble particulate filler material; The electrochemical separator assembly of claim 11.

18. 1. A method comprising: operating an electrochemical cell comprising an anode material disposed on an anode current collector, a cathode material disposed on a cathode current collector, and a separator assembly disposed between the anode material and the cathode material, the separator assembly including a first separator layer, a second separator layer, and an intermediate layer disposed between the first separator layer and the second separator layer; and modifying the operation of the electrochemical cell based on the property measured at the intermediate layer. method.

19. At least one of the first separator layer or the second separator layer includes a ceramic layer.

20. The method of claim 18.

20. At least one of the first separator layer or the second separator layer comprises a porous polymer.

20. The method of claim 18.

21. At least one of the first separator layer or the second separator layer comprises polyvinylidene fluoride (PVdF); 20. The method of claim 18.

22. The electrochemical cell comprises a lithium ion battery.

20. The method of claim 18.

23. The property measured at the intermediate layer includes a temperature of the intermediate layer.

20. The method of claim 18.

24. the intermediate layer comprises a soluble particulate filler material; 20. The method of claim 18.

25. modifying the operation of the electrochemical cell includes ceasing operation of the electrochemical cell; 20. The method of claim 18.

Citation Information

Patent Citations

  • Separator for nonaqueous secondary battery, method of manufacturing the same, and nonaqueous secondary battery

    JP2010123383A

  • Separator for nonaqueous secondary battery, and nonaqueous secondary battery

    JP2010146839A

  • Separator for nonaqueous secondary battery

    JP2010232048A

  • Separator for nonaqueous secondary battery, and nonaqueous secondary battery

    JP2011129304A

  • Separator for nonaqueous electrolyte battery and nonaqueous electrolyte battery

    JP2012049052A